ANALISIS KESALAHAN KALAM BAHASA ARAB PADA PESERTA DIDIK LEMBAGA PENGEMBANGAN BAHASA ASING (LPBA) PONDOK PESANTREN NURUL JADID PAITON PROBOLINGGO - Wijaya, Mualim; Oktaviani, Nanda Devi (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
This research was motivated by the obligation of students at the Institute for Foreign Language Development (LPBA) Pondok Pesantren Nurul Jadid Paiton Probolinggo to speak a foreign language, namely Arabic. However, in practice many of them still make mistakes in speaking Arabic. Therefore, the language skills of students are not balanced, knowing the pattern of mistakes made by students can minimize or even eliminate the errors in speaking Arabic. This study aims to identify errors in speaking Arabic in students. And knowing the cause of the error and providing the right solution to the mistakes of speaking Arabic. The research methodology used by researchers in identifying speaking errors in students is a qualitative method with a descriptive analysis approach. And the data collection techniques include: observation, interviews, and documentation. While the data analysis used by researchers is a qualitative descriptive analysis. The results of the study indicate that there are 4 components of the form of Arabic speaking errors made by students, namely: phonology, morphology, syntax, and semantic errors. And the cause of the error is the influence of the language that is known first (Mother Language), lack of understanding of Arabic language rules, musyrifah not correcting student errors so that it becomes a bad habit, and students' lack of understanding of the adjustment of the words they use (Arabic). The solution to overcome speaking errors in Arabic for these students is that musyrifah plays an active role and provides a good example in learning Arabic, Giving ta'zir (punishment) to students who make mistakes in speaking Arabic, multiplying mufrodat (vocabulary). and Eliminate the habits of students who tend to generalize Arabic with a language that is known first (mother tongue.